Analytic solutions for Tethered Satellite System (TSS) subject to internal and external torques undergoing a spin-up and spin-down maneuvers - Aw, Aaron Teik Hong; Varatharajoo, Renuganth; Romli, Fairuz Izzudin (Emerald Group Publishing, 2015)
Purpose The purpose of this paper is to develop analytic solutions for a tethered satellite system (TSS) subjected to internal tether tension moment and external aerodynamic torque for spin-up and spin-down manoeuvres.